Multimodal MRI Longitudinal Assessment of White and Gray Matter in Different SPG Types of Hereditary Spastic Paraparesis - Montanaro, Domenico; Vavla, M.; Frijia, F.; Aghakhanyan, G.; Baratto, A.; Coi, A.; Stefan, C.; Girardi, G.; Paparella, G.; De Cori, S.; Totaro, P.; Lombardo, F.; et al. (Frontiers in Neuroscience, 2020)
HSP are a group of genetically and clinically heterogeneous neurologic disorders. Hereby, we describe a relatively large group of patients (pts) affected by HSP studied at baseline (31 pts) and at follow up (mean period 28.9±8.4 months; 23 pts) with multimodal advanced MRI: high resolution T1 images for VBM analysis, MRS and DTI. An age-matched healthy control (HC) group underwent in a time schedule matched with HSP patients the same neuroimaging protocol. At the baseline VBM showed GM reduction in HSP in the right pre-frontal cortex and bilaterally in the thalami. MRS at baseline depicted in HSP patients compared to the HC group reduction of NAA/Cr ratio in the right pre-frontal region, increase of Cho/Cr ratio in the right pre-central regions, and increase of mI/Cr ratio on the left pre-central area. At cross-sectional follow up analysis and longitudinal evaluation no VBM and MRS statistical results were obtained. Tract-based spatial statistics (TBSS) analysis depicted widespread DTI brain white matter (WM) alterations in patients compared to HC at baseline, characterized by reduction of FA and increase of MD, AD and RD, confirmed on cross analysis of follow-up dataset. Longitudinal analysis of TBSS analysis in HSP patients didn't show significant variations, while applying region-based analysis we found increased FA, decreased MD and AD during follow-up in specific brain WM fibers complex. The changes were not correlated with the clinical presentation (pure vs complicated HSP), motor function and motility indexes (SPRS) or history of specific treatments (botulinum toxin). In conclusion, the cross-sectional analysis of the multiparametric MRI data in our HSP patients confirmed the no prominent involvement of the cortex in the primary motor regions, but rather of other more associative areas. On the contrary, DTI demonstrated a widespread involvement of the brain WM, including the primary motor regions, which was confirmed at follow up. The longitudinal analysis revealed an apparent inversion of tendency considering the expected evolution of a neurodegenerative process: we detected an increase of FA and a decrease of MD and AD. These time-related modifications may suggest a repair attempt by the residual central WM fibers.